Moraine as a source of gold in stream sediments and the relationship to a Shear Zone in the Rombak-Skjomen area of Norway - Whitehead, David (2010)
The Rombak-Skjomen area of northern Norway consists of a c.2.3-1.78 Ga Proterozoic basement window overlain by Phanerozoic metamorphosed sedimentary rocks from the Caledonian Orogeny. The window consists of volcanic arc and sedimentary rocks deformed during the Svecokarelian Orogeny when the area was situated on the margin of the Norrbotten craton. The area is geologically similar to other important mining areas of northern Fennoscandia such as the Skellefte District and the Gold Line of northern Sweden. Exploration for gold and base metal deposits during the 1980s produced a lot of geological, geophysical and geochemical data. Stream sediment survey data has been used together with new moraine sampling data to see if there is any relation between a recently identified shear zone and unexplained gold anomalies in nearby stream sediments (Larsen et al., 2010). Different statistical methods have been used to identify anomalous metal concentrations in stream sediment surveys to produce anomaly maps that can be used alongside the new data to identify areas of mineralisation. The area has the potential to host orogenic gold style mineralisation as has been found in other areas of northern Fennoscandia. Moraine samples have been taken in profiles across the shear zone and analysed to see if the moraine is a possible source of gold in these stream sediment anomalies and if the shear zone is gold bearing. Analysis of the moraine showed that the concentration of gold is very low and it is possible that the moraine is an indirect source of gold in stream sediment anomalies. Gold can enter moraine by weathering of gold bearing mineralisations in the surrounding bedrock, but because of its fine grained nature, it is quickly washed out of the moraine to be re-deposited in stream sediments several kilometres away from its parent rock. The area probably contains more than one type of gold mineralisation that are small, widely dispersed and have different mineralogy making them hard to locate using stream sediment sampling ...